Potential value of MicroRNA-21 as a biomarker for predicting the prognosis of patients with breast cancer: A protocol for meta-analysis and bioinformatics analysis. Issue 22 (4th June 2021) - Ding, Yunfeng; Wu, Wanbo; Ma, Zhihong; Shao, Xia; Zhang, Ming; Wang, Zhanwei
Abstract: Background: The latest global cancer data from 2020 shows that breast cancer has replaced lung cancer as the number one cancer in the world. Searching for new biomarkers of breast cancer has important clinical significance for early diagnosis, prediction of prognosis, and targeted therapy. MicroRNA-21 (miRNA-21) can be used as a new molecular marker for early diagnosis, prognosis, and treatment of tumors. However, the expression of miRNA-21 in breast cancer and its prognosis are not clear. Therefore, this study conducted a meta-analysis to further clarify the relationship between the expression of miRNA-21 in breast cancer and prognosis. At the same time, we carried out bioinformatics analysis to further analyze the possible molecular mechanism of miRNA-21, so as to provide potential clinical indicators for the diagnosis, treatment, and prognosis of patients. Methods: PubMed, Medline, Embase, Web of Science, Wanfang, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure, and other databases were used to retrieve the published relevant literatures. Include the eligible research, extract the survival data hazard ratios and 95% confidence intervals and other information. STATA16.0 software was used for meta-analysis. Download the miRNA data of breast cancer through the Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO) database. The data extracted for independent sample t test and ROC curve was drawn. OncomiR plotted the survival curve of miRNA-21 on the prognosis of breast cancer. The target genes of miRNA-21 were predicted, and the Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were analyzed. STRING database and Cytoscape construct protein-protein interaction (PPI) network to obtain Hub gene. The correlation between the expression level of Hub gene in breast cancer and the abundance of immune cell infiltration was analyzed by TIMER database and verified by Kaplan–Meien plotter database. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: In this study, meta-analysis and bioinformatics analysis were used to further explore the prognosis, mechanism, and related pathways of miRNA-21 in breast cancer. Ethics and dissemination: The private information from individuals will not be published. This systematic review also should not damage participants' rights. Ethical approval is not available. The results may be published in a peer-reviewed journal or disseminated in relevant conferences. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/R32A9.